2017
DOI: 10.14740/cr577w
|View full text |Cite
|
Sign up to set email alerts
|

Does Right Ventricular Dysfunction Predict Mortality in Hemodynamically Stable Patients With Acute Pulmonary Embolism?

Abstract: BackgroundAcute pulmonary embolism (APE) is directly responsible for 100,000 deaths annually. Right ventricular dysfunction (RVD) on admission is considered a poor prognostic factor in these patients, though existing evidence of its significance in predicting mortality in hemodynamically stable patients is still unclear. We attempted to clarify this association by doing a retrospective review.MethodsWe retrospectively reviewed electronic medical records of hemodynamically stable patients older than 18 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The discrepancy of the reported data may be explained by the fact that different morbidity and/or mortality terms were used. So far, most frequently, 30-day mortality was analyzed (9,13,15,16). However, 48-h (7), three-month (17), and 180-day mortality (18) were also investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy of the reported data may be explained by the fact that different morbidity and/or mortality terms were used. So far, most frequently, 30-day mortality was analyzed (9,13,15,16). However, 48-h (7), three-month (17), and 180-day mortality (18) were also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies identified no correlation between cardiac CT measurements and mortality rate in PE (12,13,15,16). So far, Atasoy et al.…”
Section: Discussionmentioning
confidence: 99%